2010
DOI: 10.3109/02770900903584001
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Molecular Characteristics of “Difficult” Asthma

Abstract: There is evidence of significantly different morphological characteristics and molecular mechanisms of inflammation and bronchoconstriction underlying the clinical heterogeneity of severe asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 12 publications
1
9
0
2
Order By: Relevance
“…In leukocytes and the bronchi of patients with cystic fibrosis it was shown that the content of acetylcholine is substantially reduced, leading to reduced vesicle storage and transport of nonneuronal acetylcholine [33]. With respect to gene expression of muscarinic receptors, bronchoscopic evaluation of the mucosa in asthma patients revealed an increased expression of M 3 receptor mRNA in severe asthmatics compared to patients with mild-to-moderate asthma and significantly higher levels of M 3 receptor mRNA in patients with brittle asthma [45]. A similar investigation revealed that there are significantly lower levels of the M 3 receptor mRNA in patients with COPD as compared to asthma patients, and that M 3 receptor mRNA gene expression was significantly elevated in COPD patients with bronchial hyperresponsiveness as compared with patients without bronchial hyperresponsiveness [46], indicating that different molecular mechanisms underlie the clinical heterogeneity of bronchoconstriction in severe asthma and COPD.…”
Section: Muscarinic Receptors In Obstructive Pulmonary Diseasesmentioning
confidence: 99%
“…In leukocytes and the bronchi of patients with cystic fibrosis it was shown that the content of acetylcholine is substantially reduced, leading to reduced vesicle storage and transport of nonneuronal acetylcholine [33]. With respect to gene expression of muscarinic receptors, bronchoscopic evaluation of the mucosa in asthma patients revealed an increased expression of M 3 receptor mRNA in severe asthmatics compared to patients with mild-to-moderate asthma and significantly higher levels of M 3 receptor mRNA in patients with brittle asthma [45]. A similar investigation revealed that there are significantly lower levels of the M 3 receptor mRNA in patients with COPD as compared to asthma patients, and that M 3 receptor mRNA gene expression was significantly elevated in COPD patients with bronchial hyperresponsiveness as compared with patients without bronchial hyperresponsiveness [46], indicating that different molecular mechanisms underlie the clinical heterogeneity of bronchoconstriction in severe asthma and COPD.…”
Section: Muscarinic Receptors In Obstructive Pulmonary Diseasesmentioning
confidence: 99%
“…We have previously shown that HRH1 mRNA expression was significantly up-regulated in adults (p=0.04) with asthma compared to those without asthma (10) . Selivanova et al also found that HRH1 mRNA expression is significantly higher in patients with “brittle” asthma compared to those with mild to moderate asthma suggesting a possible “dose response” (39) . Therefore in our study we wanted to determine if the difference in mRNA expression between those with and without asthma could be explained by genetic variation in genes that directly involve histamine.…”
Section: Discussionmentioning
confidence: 99%
“…Ранее нами были описаны морфологические и мо лекулярные особенности фенотипов тяжелой резис тентной к терапии БА [24][25][26]. В данном исследо вании мы дополнили группы пациентов с БА и сравнили показатели с больными ХОБЛ.…”
Section: Discussionunclassified